PENERAPAN ANALISISVALUE CHAINUNTUK MENCAPAI KEUNGGULAN BERSAING - Kandou, Cici Safitri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to identify and to analyze the value activity on the company and to find out and to analyze the application of Value Chain analysis in order to achieve competitive advantage. The research object from 2011 to 2012.The data collection technique is using interview and documentation technique while the data analysis technique is using qualitative method with descriptive approach which focuses on the current research, and some elements which become the object of research.In the companyâs activities each stage of value chain which has been identified is categorized by Value Added activities. It can be concluded from the analysis that Non Value Added activity can be eliminated so cost efficiency can be applied to 2011 and 2012. Besides, a company is necessary to support cost reduction on external chain value by developing technology in order to improve company performance to compete with other companies Keywords: Value Chain Analysis, Cost Investigation, Cost Efficiency, NVA Cost,External Value Chai